Corrosion casts: A novel application of a polyurethane resin (PU4ii) for visualizing eggshell pore morphology. (10th December 2014) - Murphy, Jason P.; Swanson, Mark T.; Jaeckle, William B.; Harper, R. Given
Abstract: Avian eggshells serve the dual purposes of protecting the developing embryo from the external environment while also facilitating the loss of water vapor and the required exchange of CO2 and O2 gases. Pores that span the eggshell enable the loss of water and trans-shell gas exchange. Although knowledge of the geometry of these spaces is necessary to generate accurate estimates of the rate of gas diffusion across the shell, few techniques exist to obtain these data. Estimates of gas conductance across eggshells are typically calculated from eggshell thickness and the size and number of the pores on the exterior eggshell surface; the trans-shell pore spaces are assumed to be cylindrical in shape. To enable the testing of this assumption, we devised a novel method to visualize the three-dimensional morphology of eggshell pores using PU4ii, a polyurethane-based resin. Casts of the pores of eggshells of the domestic chicken ( Gallus gallus ) and House Sparrow ( Passer domesticus ) were unbranched and varied in diameter throughout their length, while casts of the pores of eggshells of the Ostrich ( Struthio camelus ) revealed a complex network of interconnected spaces. The simplicity of this technique and the stability and resilience of the resulting casts provide opportunities to predict gas flux across the shell and to evaluate the morphology of eggshell pores among birds from different taxonomic groups.